Chemical speciation and removal of chromium by modified Artocarpus integer fruit peels and TOC analysis in water samples / Simon Olonkwoh Salihu - Simon Olonkwoh , Salihu (2019)
The research was planned to achieve three objectives, which are different but interconnected. They include method development for the speciation analysis of Cr, and the removal of Cr from wastewater samples using an agro-waste material as well as the method development for total organic carbon (TOC), analysis in water samples. The first method developed for speciation of Cr is based on a pre-heated customized glass tube (CGT), which supplied the heat energy required to accelerate the reaction of Cr(III) with ammonium pyrrolidinedithiocarbamate (APDC). It is a cost-effective preconcentration method for the speciation of Cr as the APDC complexes. The chromium complexes, tris(1-pyrrolidinecarbodithioato) chromium(III) and bis(1-pyrrolidinecarbodithioato)[1-pyrrolidinecarbodithio(thioperoxoato)] chromium(III) were separated with HPLC-PDA. The characterization study using FT-IR and XRD of the chromium complexes was performed. The method developed was validated by the analysis of certified reference material (CRM) SLRS-4. The second method developed for the speciation of Cr relied on the preference of the ethylenediaminetetraacetic acid (EDTA), for the trivalent chromium and the APDC for the hexavalent chromium. The EDTA was a precursor for the solid phase preconcentration of Cr(III)-EDTA complex in addition to being a masking agent. The [Cr(EDTA)]- complex ion was adsorbed onto Al2O3 (neutral) adsorbent with the aid of tetrabutylammonium bromide (TBAB) pairing agent before desorption with HCl solution. Meanwhile, the Cr(VI)-APDC complexes were preconcentrated into ethyl acetate and digested with the HNO3 solution. The electrothermal atomization atomic absorption spectroscopy, (ETA-AAS) technique was employed for the detection. The removal of Cr from wastewater was investigated by diethyldithiocarbamate (DTC) modified and unmodified Artocarpus integer fruits peels. The powdered fruit peels were treated with 5%(w/v) DTC. The FT-IR, FESEM and EDX analysis of the unmodified adsorbent (UA), the diethyldithiocarbamate modified adsorbent (DTC-MA) were performed. The determination of chromium was carried out by the ETA-AAS technique. The adsorbate-adsorbent behaviour was studied by fitting adsorption data in the linearized Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich (D-R) isotherm models. The Langmuir and Freundlich models predicted favourable adsorption. The kinetics study favoured the pseudo-second-order kinetics. The breakthrough behaviour of the column fits the Thomas and Yoon-Nelson models. The application of the method for the removal of total chromium in municipal wastewater was successful. In order to achieve the third objective, the method for TOC analysis was developed by modifying the American Public Health Association (APHA) closed-tube reflux colourimetric method. The modified TOC analysis method generates the potassium dichromate on demand from potassium monochromate hence, the required oxygen for the carbon-oxygen reaction. In addition, the chloride interference was removed with sodium bismuthate, a step that eliminated mercury sulphate from the digestion mixture. Compared to the APHA closed-tube reflux colourimetric method, the modified method reduced sample consumption by 60%, and the monochromate and silver sulphate by 33% and 60% respectively. In addition, it is more environmentally friendly compared with the APHA method. The TOC analysis was performed by the UV-Vis spectrometer.